Функціонування стійких висловів у літературознавчих працях Михайла Грушевського - Каленчук, Ю. (Лексикографічний бюлетень, 2011)
In the article proof utterances as a separate type of lexical units in modern Ukrainian
is described.The problem of transformation of phraseological units is also widely
examined. There are two types of transformation: semantic and structural-semantic –
are in the modern Ukrainian.
The classification of proof utterances in the Hrushevskyj’s “History Of Ukrainian
Literature” is сonsidered. The author distinguishes three types of proof utterances in
the “History Of Ukrainian Literature”: with and without transformation; and proof
utterances, which in modern Ukrainian function in other registration. In the article
the consequences of transformation of separate proof utterances are shown and their
accordances over are brought in modern Ukrainian.